Freemium pricing: Evidence from a large-scale field experiment - Julian Runge; Stefan Wagner; Jörg Claussen; Daniel Klapper (European School of Management and Technology (ESMT), 2016)
Firms commonly run field experiments to improve their freemium pricing schemes. However, they often lack a framework for analysis that goes beyond directly measurable outcomes and focuses on longer term profit. We aim to fill this gap by structuring existing knowledge on freemium pricing into a stylized framework. We apply the proposed framework in the analysis of a field experiment that contrasts three variations of a freemium pricing scheme and comprises about 300,000 users of a software application. Our findings indicate that a reduction of free product features increases conversion as well as viral activity, but reduces usage - which is in line with the framework's predictions. Additional back-of-the-envelope profit estimations suggest that managers were overly optimistic about positive externalities from usage and viral activity in their choice of pricing scheme, leading them to give too much of their product away for free. Our framework and its exemplary application can be a remedy.
urn:nbn:de:101:1-201702134119
Keywords: M30; M20; 650; freemium; pricing; digitization; field experimentation